The effect of bariatric surgery on health care costs: A synthetic control approach using Bayesian structural time series - Christoph F. Kurz; Martin Rehm; Rolf Holle; Christina Teuner; Michael Laxy; Larissa Schwarzkopf (Health Economics, 2019)
Surgical measures to combat obesity are very effective in terms of weight loss, recovery from diabetes, and improvement in cardiovascular risk factors. However, previous studies found both positive and negative results regarding the effect of bariatric surgery on health care utilization. Using claims data from the largest health insurance provider in Germany, we estimated the causal effect of bariatric surgery on health care costs in a time period ranging from 2~years before to 3~years after bariatric intervention. Owing to the absence of a control group, we employed a Bayesian structural forecasting model to construct a synthetic control. We observed a decrease in medication and physician expenditures after bariatric surgery, whereas hospital expenditures increased in the post-intervention period. Overall, we found a slight increase in total costs after bariatric surgery, but our estimates include a high degree of uncertainty.
Keywords: 330; bariatric surgery; Bayesian structural model; obesity; synthetic controls; time series